HUBUNGAN MOTIVASI BERPRESTASI, MINAT, DAN SIKAP DENGAN HASIL BELAJAR MATEMATIKA KELAS V SEKOLAH DASAR - Rusianingsih, Cucu; Asmara, Urai Husna; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe main issues in this research are: Achievement motivation, interest and learning attitude aiming to describe the relationship between achievement motivation, interest and attitude toward learning outcome of mathematics. This research used descriptive method with quantitative approach. Subjects in this research were the students at class V of Public Primary School 16 Pontianak City. The data obtained through observation and questionnaire instruments reveal that the achievement on motivation, interest and attitude have positive and significant relationship with the learning outcome of mathematics and therefore, it can be concluded that the learning outcome of mathematics can be predicted through achievement motivation, interest and learning attitude of students. It is suggested that teachers can improve motivation, interest and learning attitude of students through various methods as an effort to achieve the desired learning outcome of mathematics.Key words:    achievement motivation, interest, attitude, learning result of mathematics